Foreign currency borrowing of housholds in new EU member states - Attila Csajbók; András Hudecz; Bálint Tamási (Magyar Nemzeti Bank, 2010)
The post-Lehman phase of the financial crisis has exposed a number of weaknesses in the banking sectors of the European Union's New Member States (NMSs). One of these is the prevalence of lending in foreign currency. While banks themselves in these countries have not taken on sizeable currency risk directly, they passed it on to households and the corporate sector. With large depreciations taking place or looming in the region, the currency risk at households and corporates without a natural hedge is now being transformed into credit risk for the banking sector. This is creating a serious problem in maintaining financial stability and cripples monetary policy in countries where it operates primarily through the exchange rate channel. The patterns of foreign currency lending to households in NMSs vary widely both across countries and time periods. For example, FX lending to households is virtually non-existent in the Czech is close to 100 per cent of total household lending. The main goal of the paper is (1) to present the stylised facts of pre-crisis FX lending in NMSs systematically and (2) to try to explain these differing patterns in an econometric model. In order to do so, a panel database of household FX borrowing is compiled, covering 10 NMSs in the period 1999-2008. Our estimation results suggest that the degree of household FX borrowing depends on the interest rate differential, the institutional features of mortgage financing and the monetary regime. Household FX borrowing tends to be less prevalent if the interest rate differential is small, fixed interest rate mortgage financing is available and the monetary authority's 'fear of floating' is low.
Keywords: E44; E50; G21; 330; foreign currency lending; new member states; credit risk; monetary policy; Kreditgeschäft; Privater Haushalt; Währungsrisiko; Kreditrisiko; EU-Staaten (Osteuropa)